Fatigue damage quantitative evaluation of carbon fiber composites at different stress ratios based on nonlinear ultrasonic - Silong Quan; Yuhua Zhang; Peishan Lin (Results in Physics, 2023)
In order to investigate the fatigue behavior of carbon fiber composites and the influence of different stress levels on their fatigue damage characteristics, the fatigue experiments of carbon fiber composites under different stress ratios are carried out. The nonlinear ultrasonic technique is used to online detect the fatigue damage process of carbon fiber composites, the relative nonlinear coefficient β under different stress ratios and different measuring positions is analyzed with the fatigue loading period. The experimental results indicate the relative nonlinear coefficient increases significantly and the rising trend accelerates when the fatigue life of specimen reaches 50%, it is the most sensitive to the change of material microstructure by comparing other parameters and can be used as the characteristic parameter to evaluate the fatigue damage of materials. In addition, the fatigue damage factor D is proposed by analyzing the relationship between the relative nonlinear coefficient and the damage degree of materials, the nonlinear ultrasonic quantitative analysis is carried out and the fatigue damage prediction model based on the relative nonlinear coefficient is established to characterize the severity of fatigue damage of materials. Therefore, the nonlinear ultrasonic quantitative evaluation method for carbon fiber composites is established, it provides a new method and data support for quantitative evaluation of fatigue damage degree of materials by nonlinear ultrasonic method.